2022
DOI: 10.3390/antibiotics11111506
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Prevalence of Extended Spectrum β-Lactamase-Producing Escherichia coli from Dogs and Cats in Northeastern China from 2012 to 2021

Abstract: (1) Background: there has been a growing concern about pet-spread bacterial zoonosis in recent years. This study aimed to investigate the trend in drug-resistance of canine Escherichia coli isolates in northeast China between 2012–2021 and the differences in drug-resistance of E. coli of different origins in 2021. (2) Methods: E. coli were isolated from feces or anal swab samples from dogs and cats, and their antibiotic susceptibility profiles and phylogenetic grouping were identified. PCR was applied on the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 71 publications
3
8
1
Order By: Relevance
“…Compared with previous studies in Sichuan, the detection rate of MDR strains among E . coli isolates from pet dogs decreased from 100% in 2017 [ 47 ] and 70% in 2018 [ 48 ] to 54.81% in our study during 2021–2022, which was similar to the trend observed in Northeast China (which decreased from 76.92% in 2012–2013 to 62.42% in 2021) [ 43 ]. The decrease in the MDR detection rate may be due to that the relevant authorities of China have released several policies to curb the increase in antimicrobial resistance in animal-derived bacteria [ 43 ].…”
Section: Discussionsupporting
confidence: 88%
“…Compared with previous studies in Sichuan, the detection rate of MDR strains among E . coli isolates from pet dogs decreased from 100% in 2017 [ 47 ] and 70% in 2018 [ 48 ] to 54.81% in our study during 2021–2022, which was similar to the trend observed in Northeast China (which decreased from 76.92% in 2012–2013 to 62.42% in 2021) [ 43 ]. The decrease in the MDR detection rate may be due to that the relevant authorities of China have released several policies to curb the increase in antimicrobial resistance in animal-derived bacteria [ 43 ].…”
Section: Discussionsupporting
confidence: 88%
“…Although bla CTX − M −1 and bla CTX − M −15 , bla CTX − M −9 , and bla CTX − M −14 belong to the same gene group, some differences still exists in the molecular structures, which led us to a second hypothesis, that the prevalence of antibiotic-resistance genes may be related to geographic factors that affect the molecular characteristics of the genes. This hypothesis can be verified in northeastern China ( 33 ).…”
Section: Discussionmentioning
confidence: 70%
“…Zhou et al [ 56 ] conducted a study investigating the prevalence of drug resistance phenotypes and ARGs of ESBL E. coli in dogs and cats in China. E. coli is one of the most common microorganisms in the intestinal flora and is continuously exposed to antibiotic selection pressure.…”
Section: Antimicrobial Resistance (Amr) In Humans and In Animalsmentioning
confidence: 99%
“…Moreover, the study found that ESBL E. coli had a higher prevalence in cats than in dogs, which differs from the findings of other research [ 64 ]. Zhou et al [ 56 ] hypothesized that this may be due to the higher use of third-generation cephalosporins in cats compared to dogs. Cats are less likely to take oral medication or medication in food, leading to a preference for injectable preparations [ 56 , 65 ].…”
Section: Antimicrobial Resistance (Amr) In Humans and In Animalsmentioning
confidence: 99%
See 1 more Smart Citation